2006
DOI: 10.1667/rr3596.1
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Thyroid Cancer, Radiation Dose from Chernobyl, and Dose Uncertainties in Bryansk Oblast, Russia: A Population-Based Case-Control Study

Abstract: A population-based case-control study was conducted to estimate the radiation-related risk of thyroid cancer in persons who were exposed in childhood to (131)I from the Chernobyl accident of April 26, 1986 and to investigate the impact of uncertainties in individual dose estimates. Included were all 66 confirmed cases of primary thyroid cancer diagnosed from April 26, 1986 through September 1998 in residents of Bryansk Oblast, Russia, who were 0-19 years old at the time of the accident, along with two individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 17 publications
1
38
1
3
Order By: Relevance
“…One, based on 107 cases diagnosed in Belarus, found a strong relationship between estimated radiation dose and thyroid cancer, but thyroid doses were inferred for children from estimates for adults who lived in the same villages (16). Two studies, based on a total of 66 cases and individual estimates of thyroid radiation dose, found that the risk of thyroid cancer was significantly increased in a dose-dependent manner among residents of Bryansk Oblast of the Russian Federation who were exposed as children and adolescents to radiation fallout from the Chernobyl accident (17,18). Finally, a fourth case-control study of 276 patients less than 15 years of age at the time of the accident in Belarus and the Russian Federation matched with 1300 control subjects showed a strong dose-response relationship between childhood thyroid radiation dose and thyroid cancer risk (19).…”
Section: Introductionmentioning
confidence: 99%
“…One, based on 107 cases diagnosed in Belarus, found a strong relationship between estimated radiation dose and thyroid cancer, but thyroid doses were inferred for children from estimates for adults who lived in the same villages (16). Two studies, based on a total of 66 cases and individual estimates of thyroid radiation dose, found that the risk of thyroid cancer was significantly increased in a dose-dependent manner among residents of Bryansk Oblast of the Russian Federation who were exposed as children and adolescents to radiation fallout from the Chernobyl accident (17,18). Finally, a fourth case-control study of 276 patients less than 15 years of age at the time of the accident in Belarus and the Russian Federation matched with 1300 control subjects showed a strong dose-response relationship between childhood thyroid radiation dose and thyroid cancer risk (19).…”
Section: Introductionmentioning
confidence: 99%
“…A similar method of risk parameters estimation was used in Kopecky et al (2006), but the approach proposed below makes it possible to give proper weight to the structure of measured doses. Note that the SIMEX method does not require the knowledge of the probability distribution for the true activity Q tr i .…”
Section: The Simex Estimator and Its Computationally Efficient Modifimentioning
confidence: 99%
“…The current methods of risk estimation (see Health Risks from Exposure to Low Levels of Ionizing Radiation, 2006;Jacob et al, 2006;Likhtarev et al, 2006a) take into account uncertainties related to health effects, but assume that the doses are known with perfect precision and accuracy, something that is not true (Kopecky et al, 2006;Likhtarev et al, 1993;Likhtarev et al, 2003;Ron and Hoffman, 1999). Although many attempts have been made to develop mathematical tools which take into account the dose uncertainty (see Carroll et al, 2006;Hofer, 2008;Kopecky et al, 2006;Li et al, 2007;Masiuk et al, 2008), the problem has yet to be solved in a satisfactory manner.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations